The Effect of Managerial Ownership, Institutional Ownership and Debt Levels on Tax Disclosure - Tabitha Liliana Chandra; Dian Purnama Sari (Eduvest - Journal of Universal Studies, 2024)
Along with the development of the business world, the demand to become a company that has transparency and accountability is an urgent need. Disclosure transparency is one of the various alternatives that can be used in overcoming tax avoidance problems. The existence of the phenomenon of tax avoidance and the still not optimal anti-tax avoidance rules, indicates the need to encourage taxpayers to increase transparency through disclosure of the tax planning schemes used. This study uses a quantitative research approach with secondary data. The population used in this study are service companies in the infrastructure, property and real estate and logistics transportation subsectors listed on the Indonesia Stock Exchange (IDX) in the 2018-2022 period. The sampling technique used purposive sampling. The results showed that managerial ownership has a positive effect on tax disclosure. institutional ownership has a positive effect on tax disclosure. The level of debt has a positive effect on tax disclosure.